2015
DOI: 10.1007/s11626-015-9918-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mimosine on Wolbachia in mosquito cells: cell cycle suppression reduces bacterial abundance

Abstract: The plant allelochemical l-mimosine (β-[N-(3-hydroxy-4-pyridone)]-α-aminopropionic acid; leucenol) resembles the nonessential amino acid, tyrosine. Because the obligate intracellular alphaproteobacterium, Wolbachia pipientis, metabolizes amino acids derived from host cells, the effects of mimosine on infected and uninfected mosquito cells were investigated. The EC50 for mimosine was 6–7 μM with Aedes albopictus C7-10 and C/wStr cell lines, and was not influenced by infection status. Mosquito cells responded to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…3). We hypothesize that mimosine may have a major function as anti-cell proliferation of male germ cells since previous reports have demonstrated in other system about theinhibitory activities of many cancer cells, cell divisions, cell proliferations and differentiations, herbicidal, insecticide, and nematicide activities (Tawada, 1990;Wang et al;Hughes & Cook;Krude;Chung et al;Park et al;Bottini-Luzardo et al;Fallon;Nguyen & Tawata). Similar to others, the testicular histopathology, such as atrophic and germ cell degenerating seminiferous tubules, damaged by mimosine in this study was also comparable to other anti-cellular division drug demonstrated previously (Iamsaard et al, 2014;Sukhorum et al, 2016;Iamsaard et al, 2017a,b;Sampannang et al, 2017).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…3). We hypothesize that mimosine may have a major function as anti-cell proliferation of male germ cells since previous reports have demonstrated in other system about theinhibitory activities of many cancer cells, cell divisions, cell proliferations and differentiations, herbicidal, insecticide, and nematicide activities (Tawada, 1990;Wang et al;Hughes & Cook;Krude;Chung et al;Park et al;Bottini-Luzardo et al;Fallon;Nguyen & Tawata). Similar to others, the testicular histopathology, such as atrophic and germ cell degenerating seminiferous tubules, damaged by mimosine in this study was also comparable to other anti-cellular division drug demonstrated previously (Iamsaard et al, 2014;Sukhorum et al, 2016;Iamsaard et al, 2017a,b;Sampannang et al, 2017).…”
Section: Discussionmentioning
confidence: 79%
“…In addition, mimosine is responsible for herbicidal, insecticide, and nematicide activities (Tawata, 1990;Nguyen & Tawata, 2015). Indeed, mimosine also can arrest the cell cycle progression to inhibit cell proliferation of many cancer cells (Chung et al, 2012;Park et al, 2012;Bottini-Luzardo et al, 2015;Fallon, 2015;Nguyen & Tawata;Kacar et al, 2017). To provide the basic information to caution people about subfertility or infertility effects from acute consumption of the LL parts containing natural mimosine; therefore, this study attempted to investigate the acute effects of purified mimosine extracted from Leucaenaleucocephala on reproductive system in male mice.…”
Section: Introductionmentioning
confidence: 99%
“…between G 1 and S phases [106] (Perennes et al, 1993), which is consistent with the inhibition of cell division of Pisum sativum radicles and Zea mays roots by the aqueous extracts of L. leucocephala [58,59], as described in the previous section. It was also reported to block cell division in mammalian and insect cells, blocking entry into S phase from late G 1 phase and suppressing elongation of DNA replication (S phase) [89,[108][109][110][111]. The activities of nitrate reductase, peroxidase, catalase, and IAA oxidase were inhibited by mimosine treatments in Oryza sativa L. seedling [112].…”
Section: Mimosinementioning
confidence: 99%
“…Currently, there are two well‐known modes of action of mimosine on the cell cycle: (i) blocking entry into S phase (late G1 phase), and (ii) suppressing elongation of DNA replication (S phase). In mammalian cells, mimosine has been suggested to arrest the cell cycle in the late G1 phase (Lalande, ; Watson et al ., ; Hoffman et al ., ; Yin et al ., ; Andreassen and Margolis, ; Ryan et al ., ; Kubota et al ., ; Fallon, ), and for this reason, it has been utilized as synchronization agent in an attempt to clarify the biochemical events that trigger the initiation of S phase (Yoshida et al ., ; Ouhibi et al ., ; Kulp and Vulliet, ). This drug has been also put forward to prevent the progression of the cell cycle after entering the S phase (Hughes and Cook, ); specifically the initiation of new replicons (Dijkwel and Hamlin, ; Mosca et al ., ; Tsvetkov et al ., ) and elongation of progeny DNA replication.…”
Section: Mimosine and Cell Cycle Blockingmentioning
confidence: 99%